2011
DOI: 10.1007/s11430-011-4269-z
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical studies on the source region of Asian dust

Abstract: The North China and the neighbouring Mongolia in Asian Interior is characterized by extremely dry climate, resulted in one of the world's major dust emission centres. Deciphering the source region of Asian dust is critical for revealing the mechanism of the dust production, interpreting the paleo-environmental records of eolian deposits, predicting the overall environmental effects of dust, and setting the strategies for the control of contemporary dust storms. This paper summarizes the geochemical methods app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(93 citation statements)
references
References 90 publications
(174 reference statements)
5
88
0
Order By: Relevance
“…Because the NYZG section is located close to the sandy deserts in NE China (Fig. 2a), and has been demonstrated to be sourced from these areas (Xie et al, 2012;Chen and Li, 2011), the loess samples are enriched in sand-sized particles associated with short-distance transport, which accords with their proximal provenance. Therefore, we infer that variations in the content of the sand-fraction (N 63 μm) in the NYZG section should be sensitive to migration of the desert margin and to wet-dry climate oscillations within the dust sources areas, as is the case for the loess deposits in the northern CLP.…”
Section: New Evidence For the Aridification Of Ne China During The Plmentioning
confidence: 79%
See 1 more Smart Citation
“…Because the NYZG section is located close to the sandy deserts in NE China (Fig. 2a), and has been demonstrated to be sourced from these areas (Xie et al, 2012;Chen and Li, 2011), the loess samples are enriched in sand-sized particles associated with short-distance transport, which accords with their proximal provenance. Therefore, we infer that variations in the content of the sand-fraction (N 63 μm) in the NYZG section should be sensitive to migration of the desert margin and to wet-dry climate oscillations within the dust sources areas, as is the case for the loess deposits in the northern CLP.…”
Section: New Evidence For the Aridification Of Ne China During The Plmentioning
confidence: 79%
“…Provenance studies using both using Nd-Sr isotopic composition (Chen and Li, 2011;Zhao et al, 2014) and detrital zircon U-Pb age analyses (Xie et al, 2012) have demonstrated that the major source areas of the loess deposits in NE China are likely to be the upwind Horqin and Otindag sandy deserts. Therefore, the loess and adjacent sandy deserts Catena 154 (2017) [21][22][23][24][25][26][27][28][29][30][31][32] in NE China can be regarded as a coupled system, with dust source and sink formed under a semi-arid climate, which is quite distinct from the loess deposits of the CLP and their corresponding sources areas in northwestern and central China.…”
Section: Introductionmentioning
confidence: 99%
“…Washington et al, 2003;Zhang et al, 2003;Chen and Li, 2011). In the central Taklimakan Desert, continuous late Cenozoic sequences with intercalated in-situ aeolian dune sand preserve direct evidence for the Asian desertification.…”
Section: Introductionmentioning
confidence: 94%
“…The terrain of Tianshan and Mongolia also uplifted considerably during this period [5,69], and even in the late Pliocene tectonic uplift still occurred in the northern TP [6,73]. Some scholars believed that the uplift of northern TP could produce the denudation at the northern edge of the plateau, and thus provide dust material for the Asian dust source region, contributing to promoting Asian dust cycle and increasing the downstream dust flux [5,86]. Existing eolian records from oceans and continents showed that since the middle Pliocene the aridification of inland Asia was intensified and the ancient dust flux followed a significantly increasing trend at the tectonic time scale.…”
Section: Influences Of the Uplift Of Northern Tibetan Plateau Upon Thmentioning
confidence: 99%